The older adult psychotherapy treatment planner - Frazer, Deborah W.; Hinrichsen, Gregory A.; Jongsma, Arthur E. (Hoboken : John Wiley & Sons, 2011)
"Like its predecessor, The TheraScribe Older Adult Psychotherapy Treatment Planner, Second Edition provides clinicians all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payers, and state and federal agencies. In addition, this new edition has been thoroughly updated to include empirically supported, evidence-based treatment interventions for older adults with mental disorders. Geropsychologists, social workers, counselors, and other mental health professionals will appreciate the clear format of this timesaving resource" --Provided by publisher.
Includes bibliographical references and index.
Keywords: Geriatric psychotherapy; Psychotherapy for older people; Mental illness -- Treatment -- Planning; Geriatric Psychiatry -- organization & administration; Patient Care Planning; Aged; Mental Disorders -- therapy; Psychotherapy -- methods